Inward FDI skilled labour, and product differentiation in the CEEC - Aleksander Rutkowski (Journal for East European Management Studies, 2006)
The ratios of spending on R&D, advertising and marketing to sales are employed accordingly as direct determinants of the degree of vertical and horizontal product differentiation. The model is verified with direct regressions and a system of simultaneous regressions combining large firm survey with sector-level data from the UNCTAD for 13 Central and Eastern European countries. The econometric results evince that the increased demand for skilled labour (human capital) was greater than any FDI-induced labour market spillovers. As expected, this contributed to less differentiation which became more costly. Consistently, foreign-owned enterprises employed more highlyskilled employees but they reacted to more foreign investment similarly to domestic firms (so reducing the level of differentiation). – – Das Verhältnis für Ausgaben für R&D, Werbung und Marketing zu den Verkäufen wurden als direkte Determinanten für den Grad der vertikalen und horizontalen Produktdifferenzierungen genutzt. Das Model wurde mit direkten Regressionen und einem System simultaner Regressionen verifiziert welches mit großen Firmen Untersuchungen mit sector level? Daten von UNCTAD für 13 Zentral- und Osteuropäische Länder. Die wirtschaftlichen Resultate zeigen das die steigende Nachfrage nach ausgebildeten Arbeitskräften (menschliches Kapital) größer als jeder FDI-induzierte Arbeitsmarktüberschuss.Wie erwartet, führte dies zu weniger Differenzierung was kostenintensiver wurde. Ständig stellten ausländische Firmen mehr hochqualifizierte Angestellte ein aber sie reagierten auf größeres ausländisches Investment ähnlich wie inländische Firmen (so reduzierten sie das Niveau der Differenzierung).
Keywords: 650; product differentiation; business strategy; inward FDI; skilled labour; Central and Eastern Europe